An Expedition to the Ranquel Indians : Excursion a los indios ranqueles - Mansilla, Lucio V., 1831-1913 (Book collections on Project MUSE., 1997)
"Translation of 1870 Una excursión a los indios ranqueles, letters recounting Mansilla's visit with the Ranquel nation of Argentina. Translator made some cuts to the text for fluency, but their location is not indicated to the reader. Short introduction, notes, map, and glossary give historical and cultural background. Narrative flow emphasized through organization into five parts, each with short preface. Highly accomplished literary prose"--Handbook of Latin American Studies, v. 58.